MANAJEMEN KRISIS PUBLIC RELATIONS (STUDI KASUS TENTANG PERAN HUMAS PEMPROV SUMBAR DALAM MENGHADAPI KRISIS PEMBANGUNAN JALAN TOL PADANG-PEKANBARU) - Laurensius Arliman S (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research is a part of the author's final assignment when completing a master's degree in communication science at Andalas University, mid 2020 to 2022. This research explains that in order to handle a crisis by the public relations of the West Sumatra Provincial Government, public relations first recognizes the type of crisis first first, then the crisis stage, up to crisis management. Based on the research results, the type of crisis faced by the Provincial Government of West Sumatra is an immediate type of crisis, because it involves public transportation and community land acquisition. Furthermore, crisis management is carried out starting from identifying the crisis, Crisis Analysis, and Crisis Isolation. The handling carried out by the Public Relations of the West Sumatra Provincial Government must have a good impact on the company.Keywords: Crisis Management, Public Relations, Public Relations, Toll Roads.